The Effect of General Allocation Funds, Special Allocation Funds, Regional Original Income, Capital Expenditures on Economic Growth - Karmen Marpaung; Dedi Takari; Cici D Ompusunggu (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2021)
This research uses quantitative research. The data used in this study are secondary data with a period of 5 years. The data collection method uses literature study method. Documents that are the main source of data can be seen at the Central Bureau of Statistics of each Regency / City in Central Kalimantan. The data analysis used in this research is multiple linear regression analysis. The results of this study indicate that the DAU and DAK do not have a significant effect on economic growth, while PAD and capital expenditures have a significant effect on economic growth. The results of this study also show the importance of the role of local governments in managing and utilizing the realization of regional revenues to increase public productivity, for example the provision of equitable infrastructure both in villages and in cities